Yield reduction of spring wheat in relation to disease development caused by Septoria nodorum - Karjalainen, Reijo; Karjalainen, Sinikka (Agricultural and Food Science, 1990)
Effects of Septoria nodorum on the grain yields and yield components of three spring wheat cultivars were studied in Finland using artificial field inoculation over three years. At low infection level, in 1986, grain yield was reduced in all cultivars by 2—10 %, but statistically insignificantly. In 1984 severe infection reduced the grain yields of cultivars Kadett and Tähti by 27 % and 32 %, respectively, while in 1985 the yield of Tähti was reduced by 16 % and that of Kadett by 18 %. Grain weights were reduced under low disease stress by 3—5 %, while under severe disease stress the reductions were 7—20 %. Disease strongly reduced the green-leaf area duration compared with fungicide-treated plots. Examination of single tillers showed that all yield components were significantly reduced. The disease amount on second leaves correlated best with grain weight loss. Implications of these results for controlling the damage caused by S. nodorum in spring wheat are discussed.